1979
DOI: 10.1351/pac197951040913
|View full text |Cite
|
Sign up to set email alerts
|

The Pfeiffer effect, outer-sphere complexation, and the absolute configuration of dissymmetric coordination compounds

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…tartrate substrates, amino acids, or sugar derivatives) 26-28. The added chiral species may perturb the racemic equilibrium resulting in a nonracemic ground state (this is often referred to as the “Pfeiffer effect”,29-32 a term originated from a work on the enhancement of optical rotation of optically active alkaloids in the presence of labile racemic transition-metal complexes) 33,34. These differences can be detected by measurement of the circular polarization in the luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…tartrate substrates, amino acids, or sugar derivatives) 26-28. The added chiral species may perturb the racemic equilibrium resulting in a nonracemic ground state (this is often referred to as the “Pfeiffer effect”,29-32 a term originated from a work on the enhancement of optical rotation of optically active alkaloids in the presence of labile racemic transition-metal complexes) 33,34. These differences can be detected by measurement of the circular polarization in the luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that molecules associating to [LnL 3 ] n− complexes interact with the π*orbitals of the pyridine rings, 8 in analogy to phenanthroline complexes of transition metals; 46 however, we are not convinced that these interactions govern this effect. Consider that when the carboxylate groups of dipicolinate are transformed into chiral amide groups, the resulting complexes of lanthanides self-assemble in solution as enantiopure Λ or Δ complexes.…”
Section: Resultsmentioning
confidence: 77%
“…5,34,35 When the mixture of enantiomers is racemic, the emitted light is not circularly polarized; however, perturbing the equilibrium between the Λ and Δ forms generates an excess of one enantiomer and the luminescence from this mixture is circularly polarized. 31, 44,46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the earlier results, which concentrated more on equilibrium studies, were based on UV spectroscopy. Other methods, such as the use of the Pfeiffer effect [22], have also been employed.…”
Section: Formation Constants Structure and Lifetimes Of Outer Smentioning
confidence: 99%